Novel Formulation of Herbal Pesticide for Rice Cultivation: Life Sciences-Herbal Pesticide - K, Ahilandeswari; Maheswari.N, Uma (International Journal of Life Science and Pharma Research, 2022)
The irrational use of chemical pesticides has caused serious health hazards and environmental problems in developing countries including India. Hence, the Present investigation was carried out to formulate an effective Herbal pesticide against three major pests of rice like stem borers, leafhoppers and plant hoppers and to find solution for control of pest population by traditional agricultural practices. Oil of Azadirachta indica, Vitex nigundo, Ipomoea carnea, Adhatoda zeylanica and natural surfactant are the main constituents used in the formulations. Larvae of stem borers in the infected stem and hopper damaged part of the plant were selected for the study. A total of six herbal formulations at four different concentrations were sprayed on larvae of stem borers and hopper damaged parts of plants. The developed herbal pesticides have been validated in the field as well as in lab conditions and larval mortality rates were observed. After treatment, the population of pests decreased gradually and the mortality rate of larvae increased. Herbal pesticides focus on providing solutions and relief from various types of insects that cause massive damages to the plants being grown on a farm. These products were made of natural materials that have properties of killing or keeping out pests within the range of the field. The results showed that the extent of growth of these pests was less when compared to control and minimum occurrence of pest attack and Percent Dead Heart (DH) was confirmed in response to herbal formulations. The foremost benefit of this herbal pesticide is managing the Yellow Stem Borer (YSB) pest population and providing healthier cropping systems. Hence it is recommended to use this herbal pesticide for disease free sustainable cultivation of organic rice.